1981
DOI: 10.1113/jphysiol.1981.sp013655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid‐base changes on excitation‐‐contraction coupling in guinea‐pig and rabbit cardiac ventricular muscle.

Abstract: 7. Respiratory and metabolic acidoses depressed the action potential plateau and prolonged repolarization.8. The resting potential and the maximum rate of depolarization were unaffected by the above acid-base changes.9. An acidosis depressed Ca2+ influx through the slow inward channel by an amount sufficient to account for the observed contractility changes.10. it is concluded that between pH 7-6 and 6-6 the major physiological effect of an acidosis is to depress the slow inward current as a result of an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 50 publications
4
45
1
1
Order By: Relevance
“…This decrease in phase 2 amplitude of MAP is consistent with previous reports (9,19,20), which has been ascribed to a decrease in plateau-phase Ca 2+ influx (19,21). Meanwhile, with regard to the shortening of MAP duration, some studies reported that a decrease in extracellular pH shortens the action potential duration (22 -25), but the others described opposite results (26,27). It has been reported that under acidic condi- tions, H + directly binds to I Kr and I Ca channels, resulting in their current inhibitions (11,19,20,28).…”
Section: Discussionsupporting
confidence: 80%
“…This decrease in phase 2 amplitude of MAP is consistent with previous reports (9,19,20), which has been ascribed to a decrease in plateau-phase Ca 2+ influx (19,21). Meanwhile, with regard to the shortening of MAP duration, some studies reported that a decrease in extracellular pH shortens the action potential duration (22 -25), but the others described opposite results (26,27). It has been reported that under acidic condi- tions, H + directly binds to I Kr and I Ca channels, resulting in their current inhibitions (11,19,20,28).…”
Section: Discussionsupporting
confidence: 80%
“…Values of pHï and pHé in these solutions are shown in Table 1. Because Ca¥ and HCOצ form ion pairs in solution, changes to [NaHCO×] necessitated changes to [CaClµ] in these superfusates to maintain constant the ionized calcium concentration (Fry & Poole-Wilson, 1981). Solutions containing 9·6 and 48 mÒ NaHCO× contained 1·55 and 2·34 mÒ CaClµ, respectively, to maintain the same ionized calcium concentration as was present in Tyrode solution (24 mÒ NaHCO×, 1·8 mÒ CaClµ), and were checked with a Ca¥-selective electrode.…”
Section: Solutionsmentioning
confidence: 99%
“…This possibility is supported by the present experiments. Although the effects of acidosis on APD in the mammalian heart are controversial (Chesnais et al, 1975;Fry and Poole-Wilson, 1981;Sato et al, 1985;Komukai et al, 2002), we clearly showed a prolongation of the AP at different repolarization times throughout the acidosis period in the toad ventricle. The mechanism of the AP prolongation was not explored in the present work.…”
Section: Dependence Of Contractile Recovery On Ca 2+ Influx: Ncx Vs Lmentioning
confidence: 81%
“…The initial impairment of contractility is followed by a partial recovery that occurs in spite of the persistent extracellular acidosis (Mattiazzi and Cingolani, 1977b;Fry and Poole-Wilson, 1981;Cingolani et al, 1990;Pérez et al, 1993). Considerable research has been done in mammalian heart, in order to elucidate the causes of this recovery (e.g.…”
Section: Introductionmentioning
confidence: 99%